Ileal Histoplasmoma in a Patient Infected with the Human Immunodeficiency Virus (HIV) - Inocente Licetti, Augusto (2012)
We report a case of a 23-year old HIV-infected man who presented to the Emergency Department with abdominal pain, chronic diarrhea and weight loss of two months duration. A plain X-ray film of the abdomen showed dilated small bowel loops with air- fluid levels, ultrasonography of the abdomen showed intestinal dilatation and the presence of fluid in the abdominal cavity. After 8 days being hospitalized we decided to perform surgery in this patient, because of the development of peritoneal signs. We performed an exploratory laparotomy, where a perforation 40-cm distant from the ileo-cecal valve was found, surrounded by a tumoral mass. The lesion was excised and the pathology examination showed the presence of chronic inflammation and tissue repair, with a severe lymphocyte, plasma cells and macrophage infiltration was found, compatible with histoplasmosis. This condition was confirmed when the samples were stained using PAS. Intestinal histoplasmoma is a pseudotumoral lesion that may be found in patients with disseminated histoplasmosis and immune suppression.